Beyond economics: cultural factors affecting early school leaving—A systematic literature review - Brown, Martin; Gardezi, Sarah; O'Hara, Joe; McNamara, Gerry; Cassidy, Aideen; McNamara, Michael (Frontiers in Education, 2025)
Early school leaving (ESL) remains a critical challenge across Europe, with profound implications for individuals and society, encompassing economic disadvantages, social exclusion, and reduced life opportunities. This systematic literature review examines the cultural factors that underpin patterns of ESL, employing the Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) methodology to synthesize findings from 59 studies conducted across diverse European contexts between 2003 and 2023. The review delineates five primary thematic domains influencing ESL: cultural values, beliefs and behaviors; cultural and social barriers; academic barriers within schooling structures; discrimination and prejudice; and culturally constructed gender norms. Through the analysis, the review argues that cultural determinants are interwoven with socioeconomic and institutional factors, shaping educational aspirations, engagement and outcomes. The review highlights the central role of parental attitudes, cultural capital and systemic responsiveness in either mitigating or exacerbating risks of ESL. It calls for culturally responsive educational policies and practices that acknowledge the heterogeneity of student backgrounds and promote inclusive, equitable learning environments. The findings contribute to a deeper understanding of ESL's complex sociocultural dimensions and highlights targeted interventions to reduce early school leaving across the world.